Prejudice and discrimination in the everyday life of same-sex couples raising children - Tombolato, Mário Augusto; Maia, Ana Cláudia Bortolozzi [UNESP]; Uziel, Anna Paula; Santos, Manoel Antônio Dos (Programa de Pós-Graduação em Psicologia, Pontifícia Universidade Católica de Campinas, 2018)
The present study investigated the experiences of prejudice and discrimination in the everyday lives of five same-sex couples raising children. Data were collected using a questionnaire and an interview and were analyzed by thematic analysis. Participants attributed meanings to their experiences of being homoparental families: they assumed their social role as they managed to develop their own conjugality and parental projects in the struggle within a social context permeated by the hegemony of heteronormative values. The participants experienced prejudice related to their lifestyle and attained parenthood status, challenging social norms and gender stereotypes. However, it was also found that attitudes of willingness and perseverance in their fight for their rights proved to be protective measures against prejudice and social intolerance. A limited number of studies have examined the prejudice and discrimination towards same-sex families in Brazil; therefore, there is a need for greater visibility and further discussion about this phenomenon.

Este estudo investigou as vivências de manifestações de preconceito e discriminação no cotidiano de cinco casais homossexuais com filhos. Os dados coletados por questionário e entrevista foram analisados pela técnica de análise temática. Os participantes atribuíram significados às suas vivências enquanto famílias homoparentais: assumiram o protagonismo social ao conseguirem gerar seus projetos de conjugalidade, maternidade e paternidade no embate com o contexto social permeado pela hegemonia dos valores da heteronormatividade. Os preconceitos vivenciados pelos participantes foram dirigidos aos seus modos de viver e por assumirem a parentalidade, desafiando convenções sociais e estereótipos de gênero. Entretanto, também se observou que atitudes como disposição e perseverança na luta pelos seus direitos demonstraram ser medidas protetoras contra o preconceito e a intolerância social. Um limitado número de estudos tem avançado na temática do preconceito e da discriminação voltados à família homoparental brasileira; logo, é inadiável dar visibilidade à discussão desse fenômeno.
Preconceito e discriminação no cotidiano de casais homossexuais com filhos
Keywords: Family; Homosexuality; Parents; Prejudice; Família; Homossexualidade; Pais; Preconceito